PERAN PEMUDA DALAM PENGEMBANGAN DESA WISATA DI DESA MENTAYAN KECAMATAN BANTAN KABUPATEN BENGKALIS - Khairul Fahmi; Yusmar Yusuf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The purpose of this study was to describe the role of youth in the development of a tourist village in Mentayan Village and to find out the active and passive roles that influence the role of youth in the development of a tourist village in Mentayan Village. This research uses a qualitative approachthe results are presented descriptively.Data collection was carried out using observation, interview and documentation techniques with the research subjects being village heads, heads of BUMDES, community leaders, chief managers, youth around Mentayan Tourism Village. Source of data using primary data and secondary data. Data analysis used is qualitative analysis with data collection steps, documents, facts in the field and drawing conclusions.The research results obtained in this study are: (1) The role of youth is very important in the development of tourist villages, namely: youth is one of the factors that form tourist villages, youth are the next generation to create new things in tourist villages. the role of youth is very helpful in launching all activities and management in the development of tourist villages. (2) the active role of youth and the passive role of youth in the development of a tourist village, namely: the role of youth in making and managing a tourist village into a good place through beautiful photo spots and a good scenic atmosphere makes the tourist village one of the places that must be visited becausethe beauty and friendliness of youth and the surrounding community, some of the passive roles of youth are too focused on online games. Keywords: Role, Youth, Mentayan Tourism Village